ZEOPONIC AS GROWTH MEDIA OF HORTICULTURE PLANTS - Suwardi Suwardi; M. Bagus Pangestu (Jurnal Zeolit Indonesia, 2004)
Hydroponic is a method to growing up plant on non soil plant growth media (PGM) such as water, sand, gravel, carbon etc which mixes with other materials needed to grow the plants. The weaknesses of PGM are the low buffering capacity on electrical conductivity which can disturb the absorbtion of nutrients by plants. This can be caused by the low cation exchange capacity rate on the holding capacity of the media on nutrients. PGM such as zeoponic is made from zeolite and other materials like compost, peat moss, vermiculite, fertilizer, etc. The superiority of zeolite namely high cation exchange capacity and fertilizing efficiency rate, suitable for seed germination media and horticulture plant growth media, stable and more attractive performance. With these superiority, zeoponic became an alternative PGM which potential to increase horticulture plant production and to accommodate germination, both plantation and forestry. More over zeoponic made hydroponic became much easier to be done.